O direito de construir perante a função social da propriedade urbana - Bicudo, Pedro Marino (2008)
The following study analyses the relation between the right to build and the right of property, with focus on the principle of the social function of the urban property. The recent discussions regarding such principle and the fact that the Municipality is the competent governmental body to propose and execute its strategic general zoning plan and take decisions regarding urbanism matters, would be indicatives, under the understanding of the Urbanism Law doctrine, that the right to build and the right of property are unrelated. However, a different conclusion is reached upon the analysis of the constitutional and infra-constitutional rules regarding the matter. Even if the principle of social function of the property is considered as a fundamental right this does not lead to the exclusion of the right of property, nor to its separation of the right to build. Preserving the harmony of principles, the present work concludes that the right of property and the principle of the social function of the property must coexist, one not interfering on the existence of the other. This discussion is restricted to the existing relation between the right to build and the right of urban property. The epistemological restriction is justifiable, as the essential content of urban and rural properties are different. Regarding the urban property, it is clear that the essential content is precisely the right to build. Therefore, since the principle of social function of the property and all infra-constitutional ramifications related the theme do not change the minimal and essential content of the right of urban property, as well as its purpose and extension, the conclusion is that the urban property holder continues to be the rightful owner of the right to build